Predation of herps by spiders (Araneae) in the Brazilian Cerrado - Maffei, Fábio [UNESP]; Ubaid, Flávio Kulaif [UNESP]; Jim, Jorge [UNESP] (My University, 2010)
Two events of predation of herps by spiders in the Brazilian Cerrado are reported here. A lizard Micrablepharus atticolus (Sauria: Gymnophthalmidae) was found being preyed upon by Lycosa erythrognatha (Araneae: Lycosidae) and a frog Physalaemus cuvieri (Anura: Leiuperidae) was seen being preyed upon by Ancylometes sp. (Araneae: Ctenidae).
Keywords: Amphibia; Anura; Frog; Lacertilia; Lizard; Prey; Reptilia; Squamata